Assessment of changes to Saudi Labour Law regarding unfair dismissal of employees. Issue 4 (2nd December 2020) - Alharbi, Meshal Nayef
Abstract : Purpose: Saudi Arabia recently amended the Labour Law provisions governing the unfair dismissal of employees in the private sector. The previous version of the legislation, which had been in force for many years, had entitled employees to demand reinstatement or make a claim for fair financial compensation equal to the damages sustained. The recent amendments eliminated the right of a dismissed employee to seek reinstatement and also revised the rules relating to monetary compensation. The purpose of this paper is to critically analyse and evaluate the new approach, which has been criticized heavily. In addition, it suggests feasible alternative ways to handle unfair employee dismissal, which can be incorporated into the current Saudi Labour Law. Design/methodology/approach: This paper presents an analysis of the existing approach to dealing with unfair employee termination in the Saudi Labour Law. It is based mainly on information collected from various legal materials, such as books, review of judgments issued by the Commission for the Settlement of Labour Disputes in Saudi Arabia and relevant Islamic rules. Findings: The results of this examination clearly show that there are several flaws in the current approach to dealing with the issue of unfair dismissal of employees. To correct this situation, workable approaches have been suggested for possible consideration and incorporation into the Saudi Labour Law. Originality/value: To the author's knowledge, this is the first academic study to analyse the current approach to handling unfair employee dismissal in the Saudi Labour Law.